A possible aid in targeted insertion of large DNA elements by CRISPR/Cas in mouse zygotes. Issue 2 (17th January 2016) - Nakao, Harumi; Harada, Takeshi; Nakao, Kazuki; Kiyonari, Hiroshi; Inoue, Kenichi; Furuta, Yasuhide; Aiba, Atsu
Summary: The CRISPR/Cas system has rapidly emerged recently as a new tool for genome engineering, and is expected to allow for controlled manipulation of specific genomic elements in a variety of species. A number of recent studies have reported the use of CRISPR/Cas for gene disruption (knockout) or targeted insertion of foreign DNA elements (knock‐in). Despite the ease of simple gene knockout and small insertions or nucleotide substitutions in mouse zygotes by the CRISPR/Cas system, targeted insertion of large DNA elements remains an apparent challenge. Here the generation of knock‐in mice with successful targeted insertion of large donor DNA elements ranged from 3.0 to 7.1 kb at the ROSA26 locus using the CRISPR/Cas system was achieved. Multiple independent knock‐in founder mice were obtained by injection of hCas9 mRNA/sgRNA/donor vector mixtures into the cytoplasm of C57BL/6N zygotes when the injected zygotes were treated with an inhibitor of actin polymerization, cytochalasin. Successful germ line transmission of three of these knock‐in alleles was also confirmed. The results suggested that treatment of zygotes with actin polymerization inhibitors following microinjection could be a viable method to facilitate targeted insertion of large DNA elements by the CRISPR/Cas system, enabling targeted knock‐in readily attainable in zygotes. genesis 54:65–77, 2016. © 2016 Wiley Periodicals, Inc.